2020
DOI: 10.1186/s12888-020-02646-5
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mental distress in a rural Ethiopian community: a critical examination of psychiatric labels

Abstract: Background: Perinatal mental distress poses a heavy burden in low-and middle-income countries (LMICs). This study investigated perceptions and experiences of perinatal mental distress among women in a rural Ethiopian community, in an effort to advance understanding of cross-cultural experiences of perinatal mental distress. Methods: We employed a sequential explanatory study design. From a population-based cohort study of 1065 perinatal women in the Butajira Health and Demographic Surveillance Site, we purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Although not directly associated with our examination of the BIMF, the absence of selfreported depression among the mothers in this research might be important. Other research has indicated that perinatal depression is likely to be approximately 13% among mothers in middleand low-income countries in general [29] and in Ethiopia, specifically [30], and as high as 33%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not directly associated with our examination of the BIMF, the absence of selfreported depression among the mothers in this research might be important. Other research has indicated that perinatal depression is likely to be approximately 13% among mothers in middleand low-income countries in general [29] and in Ethiopia, specifically [30], and as high as 33%…”
Section: Discussionmentioning
confidence: 99%
“…Although not directly associated with our examination of the BIMF, the absence of self-reported depression among the mothers in this research might be important. Other research has indicated that perinatal depression is likely to be approximately 13% among mothers in middle- and low-income countries in general [29] and in Ethiopia, specifically [30], and as high as 33% in rural parts of Ethiopia [31]. The discrepancy between those statistics and the mothers’ self-reports in this research suggests that responses on the BIMF in this research might be regarded with a degree of reservation despite the mothers having been assured by the data collectors of confidentiality concerning their responses in order to discourage them from creating an inaccurately favorable impression.…”
Section: Discussionmentioning
confidence: 99%
“…way in which depression and anxiety manifest and the non-biomedical causal attributions of depressive/anxiety symptoms in this socio-cultural context [43] could have contributed to the low detection by mental health professionals applying Western diagnostic criteria [42]. The diagnosis and presentation of depression in Ethiopian culture appears to include a combination of anxiety, somatic and depressive symptoms rather than typical DSM criteria of depression [44].…”
Section: Plos Onementioning
confidence: 99%
“…Like other developing country children's mental health needs are high and evident from early childhood throughout adolescence. In a recent study, mothers reporting perinatal depressive symptoms indicated that they were more comfortable conceptualizing these experiences as distress brought on by an external source, such as poverty, physical ill-health or supernatural factors rather than being mental health related (Molenaar et al, 2020 ). Authors noted that Westernized explanations of mental health symptomology would be inconsistent with their cultural beliefs.…”
Section: Ethiopian Context Barriersmentioning
confidence: 99%
“…Community supports evident in westernized social worker practice, can be seen as similar to the popular practice among Ethiopian Orthodox Christians called Yenesha Abat—which involves a priest serving as a family mentor or guide who makes frequent visits to the home. Again, these similarities appear to be a promising link from a traditional healing relationship to a westernized therapeutic service (Zeleke et al, 2019 ; Molenaar et al, 2020 ).…”
Section: Traditional and Western Approaches To Mental Health Needs And Treatmentmentioning
confidence: 99%